Ionic diffusion into the peripheral area of a glow discharge in the electronegative gases - Golovitskii Alexander (St. Petersburg Polytechnical University Journal: Physics and Mathematics)
In the paper, the effect of negative ion diffusive penetration from the central space representing the ion-ion plasma on the electron-ion plasma located in the peripheral area of a positive column of a glow discharge in the strong electronegative gases has been studied. The said penetration was shown to be responsible for formation of an electron density profile being close to linear within the peripheral area and also for sufficient reduction of its transverse size. The explicit approximate analytic expressions for parameters of electron density profile were found. The results of a specially conducted computational experiment were compared with those obtained through the approximate solution, and their good agreement was established (the error did not exceed 13%). The research carried out is important for correct quantitative evaluations of ionization rate, electron temperature and a longitudinal field in a positive column of an electronegative glow discharge.